A computationally efficient C0 continuous finite element model for thermo-mechanical analysis of cross-ply and angle-ply composite plates in non-polynomial axiomatic framework. (April 2023) - Joshan, Yadwinder Singh; Soni, Aakash; Grover, Neeraj
In the present article, the thermo-mechanical bending response of multi-layered composite plates is investigated in the framework of inverse-hyperbolic shear deformation theory using a generalized finite element model. The mathematical development is carried out under the assumptions of linear structural kinematics for the materials following generalized Hooke's law. Energy-based finite element formulation and the principle of minimum potential energy are employed to develop the finite element governing equations. A computationally efficient C 0 continuous finite element formulation is developed to examine the response of laminated composites subjected to constant, linear, and non-linear temperature change. Numerical analyses are carried out for composite laminates considering various lamination sequences (cross-ply as well as angle-ply), boundary conditions, loading conditions, span-thickness ratio, etc. The present results are compared with the existing analytical and numerical results and their agreement is observed. The effect of fiber orientation angle on bending response is analyzed to enable the optimal design of laminated composite structures under thermo-mechanical loading.